MODL-24. AN ORGANOTYPIC CHUNK CULTURE TECHNIQUE TO STUDY DISEASE MECHANISM AND DEVELOP TARGETED THERAPEUTICS FOR PEDIATRIC ADAMANTINOMATOUS CRANIOPHARYNGIOMA. (4th December 2020) - Vijmasi, Trinka; Prince, Eric; Hengartner, Astrid; Staulcup, Susan; Griesinger, Andrea; Donson, Andrew; Gilani, Ahmed; Foreman, Nicholas; Hankinson, Todd
Abstract: BACKGROUND: Advances in the treatment of Adamantinomatous Craniopharyngioma (ACP) face challenges with translation to clinical study due to the absence of robust culture models of the disease. We developed a technique for culturing human ACP tissue in an organotypic chunk culture format that retains the tumor microenvironment for a duration sufficient to evaluate potential targeted therapeutics. METHODS: Intraoperatively collected tumor tissue from pediatric ACP was cut into volumes of approximately 3 mm 3 and rested over a semi-permeable insert placed in the wells of a 6-well plate. Specimens were cultured in (1) Control media, media containing (2) Tocilizumab, (3) Trametinib, and (4) combination of Tocilizumab and Trametinib, for 24 and 96 hours. Specimens were harvested for paraffin embedding, protein and gene expression assays. Supernatants were collected to assay secreted components. Paraffin embedded specimens were sectioned and stained for H&E, Pan-CK, Beta-Catenin, cleaved Caspase-3, Ki-67, and Phospho-ERK. RESULTS: H&E staining revealed characteristic histologic features of ACP with epithelial cells with palisading nuclei, wet keratin and ghost cells. Tumor sections were markedly positive for epithelial cell markers, Pan-CK and Beta-Catenin. Ki-67 and cleaved Caspase-3 were restricted to a small fraction of cells, indicating low index of proliferation and apoptosis under the culture conditions. The response to drug treatments shall be determined using gene expression assays and evaluation of the secreted components. CONCLUSION: The organotypic chunk culture technique appears to maintain the viability and integrity of ACP tumors for several days and may serve as an appropriate model for pre-clinical studies to develop targeted therapeutics for pediatric ACP.